2016
DOI: 10.4088/jcp.15m09844
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Specific Clinical Symptoms of Behavioral Variant Frontotemporal Dementia Versus Differential Psychiatric Disorders in Patients Presenting With a Late-Onset Frontal Lobe Syndrome

Abstract: In daily clinical practice, specific subtyping of clinical symptoms in patients with late-onset frontal lobe syndrome may aid in differentiating bvFTD patients from psychiatric patients and may provide guidance in patient management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
13
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 15 publications
5
13
0
1
Order By: Relevance
“…Our results suggest that positive symptoms, such as inappropriateness, hyper-orality, aggression, and stereotyped behaviour are present in the early phase of bvFTD, as positive FBI scores at the initial visit have been previously shown to be different between diagnostic groups (Dols et al, 2016;) -but may not change any further over the time period studied in this study, the diagnostic stage. Since our follow-up duration was 2 years, I cannot be excluded that an increase of positive symptoms occurs in later stages of bvFTD.…”
Section: Discussionsupporting
confidence: 47%
See 3 more Smart Citations
“…Our results suggest that positive symptoms, such as inappropriateness, hyper-orality, aggression, and stereotyped behaviour are present in the early phase of bvFTD, as positive FBI scores at the initial visit have been previously shown to be different between diagnostic groups (Dols et al, 2016;) -but may not change any further over the time period studied in this study, the diagnostic stage. Since our follow-up duration was 2 years, I cannot be excluded that an increase of positive symptoms occurs in later stages of bvFTD.…”
Section: Discussionsupporting
confidence: 47%
“…Negative symptoms decreased in psychiatric cases, potentially related to treatment. Previous studies have shown that increased FBI positive symptoms at the initial visit have a relatively high potential to discriminate bvFTD from psychiatric diagnoses, (Boutoleau-Bretonniere et al, 2012;Dols et al, 2016;. Conversely, the distinctive trajectory for the FBI in bvFTD, psychiatric and other neurodegenerative disorders was predominantly driven by negative symptoms rather than positive symptoms.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Although the distinction between bvFTD and psychiatric disorders is a major diagnostic dilemma, especially in the early stages of disease,3,5,21 knowledge on psychotic symptoms in bvFTD based on this common broad definition of psychosis cannot be ignored. In one of the previous papers,22 the authors of the present study found that a positive history of psychiatric illness, male gender, lower Stereotypy Rating Inventory (SRI) scores, and higher Montgomery–Asberg Depression Scale scores were predictors of the diagnosis of a psychiatric disorder versus bvFTD, but a systematic prospective study on the broad definition of psychosis in bvFTD has not been published yet. Whether specific psychotic symptoms of bvFTD are unique and they can distinct bvFTD from psychiatric disorders, and vice versa, would help the clinician considerably in daily practice from a diagnostic perspective.…”
Section: Introductionmentioning
confidence: 52%